A Reasoning Technique for Taxonomy Expert System of Living Organisms - anita desiani; Firdaus Firdaus; Sri Indra Maiyanti (Annual Research Seminar (ARS), 2016)
Taxonomy of living organisms can help scientists to sort organisms in order and help them to identify new organisms by finding out which their groups. It also is easier to study organisms when they are sorted in groups. Taxonomy of living organisms system is a important basic part of ecology system. Researcher should know about any organisms that they noted in an ecology. Integration between classification taxonomy of Living Organisms and technology  information will have many advantages for researchers and ecology information system. The expert system is one solution to help the problem of classification of living organisms that are authentic and novelty, and can provide advice to the user when the user needs an information about a living organism. One of the important things on the expert system is Reasoning technique. This paper used Production rule as Reasoning technique. Production rule has two reasoning method; forward chaining and backward chaining. Forward chaining method with backward chaining modified is used for inference engine in taxonomy expert system of living organisms. The method is actually forward chaining but in reasoning proccess it takes one hyphothesis of taxonomy level to help the process so the process can be faster to find solution for identification of living organisms.